2014
DOI: 10.7213/estud.biol.36.086.ao14
|View full text |Cite
|
Sign up to set email alerts
|

Macrofauna associada à Nidularium Lem. (Bromeliaceae) de diferentes estratos verticais em um fragmento de Floresta com Araucaria, Curitiba, Paraná, Brasil

Abstract: As bromélias são plantas epífitas, terrestres ou rupícolas, que em cujaroseta pode se acumular grandes volumes de água, detritos orgânicos eabrigar uma comunidade fitotélmica particular. O objetivo do presenteestudo foi verificar a composição, variação vertical, temporal e analisaríndices ecológicos da macrofauna associada ao gênero Nidularium. A áreade estudo situa-se em um fragmento de Floresta Ombrófila Mista, anexo aoZoológico Municipal de Curitiba. Duas campanhas de amostragem foramrealizadas: uma no outo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The unique architecture of plants from the Bromeliaceae is essential for many arthropods (Dias et al., 2014 ; Pereira & Quirino, 2008 ). Due to the complexity of their structure, the bromeliads offer all those features found in this type of habitat (see Dias & Brescovit, 2004 ; Hernández‐Baz et al., 2011 ; Panizon et al., 2014 ). Previous studies indicated that bromeliads are biodiversity amplifiers and key elements in the structuring of communities (Gonçalves‐Souza, Brescovit, et al., 2010 ; Jorge et al., 2021 ; Laviski et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unique architecture of plants from the Bromeliaceae is essential for many arthropods (Dias et al., 2014 ; Pereira & Quirino, 2008 ). Due to the complexity of their structure, the bromeliads offer all those features found in this type of habitat (see Dias & Brescovit, 2004 ; Hernández‐Baz et al., 2011 ; Panizon et al., 2014 ). Previous studies indicated that bromeliads are biodiversity amplifiers and key elements in the structuring of communities (Gonçalves‐Souza, Brescovit, et al., 2010 ; Jorge et al., 2021 ; Laviski et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The unique architecture of plants from the Bromeliaceae is essential for many arthropods (Dias et al, 2014;Pereira & Quirino, 2008). Due to the complexity of their structure, the bromeliads offer all those features found in this type of habitat (see Dias & Brescovit, 2004;Hernández-Baz et al, 2011;Panizon et al, 2014).…”
Section: Introductionmentioning
confidence: 99%